Investigation of the quality of the groundwater and the nitrate pollution hazards to human health in the desert region of Algeria - Lakhdari, Alia Sara; Bouselsal, Boualem (Ecological Questions, 2024)
Groundwater in the desert zone is important for supporting all life forms in these regions. This research focused on analyzing the quality of groundwater and the threats posed by nitrate contamination in the Continental Intercalary Aquifer (CI) in the Adrar region. Twenty-five groundwater samples were collected and assessed for pH, electrical conductivity, and major ions, employing hydrochemical diagrams, multivariate statistical analysis, and indices such as the Pollution Index of Groundwater (PIG), Nitrate Pollution Index (NPI), and Health Risk Assessment (HRA).The findings revealed the typical order of ion concentrations: Na+ > Ca2+ > Mg2+ > K+ for cations and Cl- > SO42- > HCO3- > NO3- for anions. These concentrations result from natural processes like evaporation and the dissolution of evaporites, along with anthropogenic influences, primarily from agricultural and urban sources. The PIG values categorized 28% of samples as having insignificant pollution, 48% as low, and 24% as high. Moreover, NPI results showed that 24% of samples had insignificant pollution, 44% displayed mild pollution, and 32% were moderately polluted. The Health Risk Assessment highlighted significant non-carcinogenic risks due to nitrate exposure. Hazard quotient values exceeded the safe threshold of 1 in 80% of samples for infants, 76% for children, and 64% for adults, indicating significant health risks. These findings underscore the critical need for targeted treatment strategies to ensure safe drinking water for the region’s population. This comprehensive analysis demonstrates the critical interplay between natural and human factors in shaping groundwater quality and emphasizes the importance of continued monitoring and intervention to protect public health.